Cloning and functional characterization of an isopentenyl diphosphate isomerase gene from Tripterygium wilfordii. (5th November 2015) - Tong, Yuru; Zhang, Meng; Su, Ping; Zhao, Yujun; Wang, Xiujuan; Zhang, Xianan; Gao, Wei; Huang, Luqi
Abstract: Tripterygium wilfordii Hook.F. is one of the most valuable medicinal plants because it contains a large variety of active terpenoid compounds, including triptolide, celastrol, and wilforlide. All of the pharmacologically active secondary metabolites are synthesized from the 2‐ C ‐methyl‐d ‐erythritol 4‐phosphate and mevalonate pathway in the isoprenoid biosynthetic system. The key step in this pathway is the isomerization of dimethylallyl diphosphate and isopentenyl diphosphate, which is catalyzed by isopentenyl diphosphate isomerase (IPI). In the present study, a full‐length cDNA encoding IPI (designate as TwIPI, GenBank accession no.KT279355) was cloned from a suspension of cultured cells from T. wilfordii . The full‐length cDNA of TwIPI was 1, 564 bp and encoded a polypeptide of 288 amino acids. The bioinformatics analysis showed that the deduced TwIPI sequence contained the TNTCCSHPL and WGEHELDY motif. The transcription level of the TwIPI in the suspension cells increased almost fivefold after treatment with methyl jasmonate as an elicitor. A functional color assay in Escherichia coli indicated that TwIPI could promote the accumulation of lycopene and encoded a functional protein.